How allosteric mutations control ligand binding in Lipocalin protein: odorant binding protein as a test case - Maxence Lalis; Lucie Moitrier; Miriam Jäger; Cornelia Meinert; Marine Brulé; Christine Belloir; Nykola C. Jones; Søren V. Hoffmann; Sébastien Fiorucci; Steffen Wolf; Loïc Briand; Jérémie Topin (Cellular and Molecular Life Sciences)
Abstract Lipocalins are a family of proteins found in mammals that are essential for the binding and transport of various molecules, but the mechanisms underlying their target recognition are still unclear. To answer this question, we studied odorant-binding proteins (OBPs), a specific type of lipocalin involved in chemical communication and olfaction. Using an integrative approach combining numerical modelling and experimental validation, we identified key structural regions that regulate the entry of molecules into the binding pocket. Modification of these regions disrupts molecular recognition, highlighting their importance for function. In addition, we found that changes in distant parts of the protein influence binding, shedding light on allosteric mechanisms. These results advance our understanding of lipocalin function and open up avenues for the design of proteins with targeted binding properties.